Knowledge, Dental Anxiety, and Patient Expectations During the COVID-19 Pandemic - Yuanita Lely Rachmawati; Isabela Anjani; Anggiona Dwi Nawang Sasi (Association of Support to Oral Health Research (APESB), 2023)
Objective: To assess the knowledge, dental anxiety, and expectations regarding dental services during the COVID-19 pandemic. Material and Methods: The respondents were Indonesian citizens above 18 years old. An online Google survey was administered using a structured questionnaire with a snowball sampling technique. Survey items comprised knowledge related to COVID-19, dental anxiety assessed using the modified DAS (Dental Anxiety Scale) and expectations regarding dental services using four dimensions of dental service quality. All questionnaires were tested for reliability and indicated acceptable and good agreement. The data were analyzed descriptively. Results: A total of 553 responses were analysed. Most respondents were female (72.9%), 76.7% knew of recommendations to postpone dentist visits and 86.8% knew methods of preventing COVID-19 transmission. More than 70% of respondents knew the precaution procedures in the dental office during COVID-19, and only 27.9% had moderate-severe anxiety. Most respondents' expectations regarding dental services during the pandemic era were related to the quality domain of reliability and responsiveness. Conclusion: Respondents knew about COVID-19 transmission and prevention, emergency conditions warranting a visit to the dentist and the procedures used at the dental office. Most respondents stated that they were not anxious about visiting a dentist during the pandemic. The respondents expect the dentist to provide sufficient information to improve oral health and treatment plan.